Diagnosis, presentation and initial severity of Autoimmune Hepatitis (AIH) in patients attending 28 hospitals in the UK. (12th April 2018) - Gordon, Victoria; Adhikary, Ratul; Appleby, Victoria; Das, Debasis; Day, James; Delahooke, Toby; Dixon, Selena; Elphick, David; Hardie, Claire; Hoeroldt, Barbara; Hooper, Patricia; Hutchinson, John; et al.
Abstract: Background & Aims: There is limited information regarding patients with AIH outside relatively few large centres. We describe here the presenting features of patients with AIH, collected as part of an audit involving 28 UK hospitals. Methods: Patients (incident since 1/1/2007 or prevalent since 1/1/2000) were ≥18 years and either met 1999 International AIH Group (IAIHG) diagnostic criteria (n = 1164), or received immunosuppressive therapy for clinically diagnosed AIH (n = 103). Results: Of 1267 patients (80% women, 91% Caucasian, age (median(range)) 55(8‐86) years, 0.5% had acute viral hepatitis (CMV/EBV/HEV); 2% were taking Nitrofurantoin and 0.7% Khat. Twenty‐one percent had clinical decompensation and/or a MELD score of >15. Time from first abnormal liver tests to diagnosis was ≥1 year in 19% and was longer in jaundiced vs non‐jaundiced patients. HBV and HCV serology were undocumented in 4%, serum immunoglobulins in 31% and autoantibodies in 11%‐27%. When documented, ≥1 antibody was present in 83%. LKM‐1‐positive and autoantibody‐negative patients had more severe disease. Histological cirrhosis was reported in 23%, interface hepatitis 88%, predominant lymphocytes/plasma cells 75%, rosettes 19% and emperipolesis 0.4%. Only 65% of those meeting 1999 IAIHG criteria also met simplified IAIHG criteria. University Hospitals compared to District General Hospitals, were more likely to report histological features of AIH. Conclusions: This cohort from across the UK is older than other multicentre AIH cohorts. One‐fifth had decompensation or MELD >15. Diagnosis was delayed in 19%, diagnostic testing was incomplete in one‐third and rosettes and emperipolesis were infrequently reported.